Loss of a major toxin gene cluster defines a metabolic schism and host-specific virulence in Botrytis pseudocinerea - Victor Coca-Ruiz; Adrián García-Barba; Josefina Aleu; Isidro G. Collado (PLoS ONE, 2026)
Botrytis pseudocinerea is a cryptic fungal species, sympatric with the notorious plant pathogen Botrytis cinerea , yet possessing distinct ecological traits including intrinsic fungicide resistance. Despite this advantage, B. pseudocinerea rarely dominates agricultural ecosystems, presenting an ecological paradox. This study resolves this paradox by defining the unique pathogenic identity of B. pseudocinerea isolate VD165. We demonstrate that VD165 exhibits superior vegetative growth and stress tolerance compared to B. cinerea B05.10, coupled with heightened virulence on solanaceous hosts (tomato, tobacco) but reduced virulence on grape. A comprehensive bio-guided chemical investigation reveals a fundamental metabolic schism: the constitutive and infection-induced upregulation of botcinin polyketides (via Bcboa6 / Bcboa9 ) contrasted with the complete functional loss of the botrydial sesquiterpene pathway. This loss is biochemically confirmed by the significant accumulation of the upstream precursor mevalonolactone. This chemotype, loss of botrydial and compensatory super-activation of botcinins, phenocopies B. cinerea Δ Bcbot2 mutants, establishing B. pseudocinerea as a “natural knockout” model that validates the inverse regulation of these major toxin families. We propose that this “evolution by subtraction” is a lineage-specific adaptation shared with the sister species B. fabae , driving host specialization and defining the ecological niche of B. pseudocinerea .